Uluslararası krizlerin göçmenlerin hareket fikirleri üzerindeki etkisi Türkiye Kovid-19 örneği - Taş, Şeyma Nur Tırımoğlu (My University, 2022)
Göç kavramı ilk çağlardan itibaren insanoğlunun ayrılmaz bir parçası olmuş ve beraberinde pek çok değişimi getirmiştir. Modern devlet kavramının ortaya çıkışı ve sınır geçişlerinin sınırlandırılması ile birlikte ise bu hareketlilik yasal ve yasal olmayan şeklinde bir ayrıma uğramıştır. İnsan arz ve talebinin söz konusu olduğu çağımızda büyük insan hareketlilikleri beraberinde göç krizlerini doğurabilirken farklı uluslararası krizler ise bu hareketlilikleri doğurma potansiyeli taşımaktadır. Sağlık temelli bir uluslararası kriz olan Kovid-19 sürecinde ise dünya genelinde hareketlilik uzun sayılabilecek bir süre yasa dışı olarak nitelendirilmiştir. Yaşanan bu sürecin hayatlarında pek çok dezavantaj barındıran göçmenler üzerindeki etkilerinin hareket fikirleri bağlamında incelenmesi gerçekleştirilecektir.

The concept of migration has been an inseparable part of human beings since the early ages and brought many transformations with it. With emergence of the modern state concept and the restriction of border crossings, this mobility has been more clearly divided into legal and illegal. In our age, where human supply and demand is in question, large human movements express a situation that needs to be controlled from the point of view of states. International crises, on the other hand, have the potential to cause great movements in terms of their results. However, during the Covid-19 process, which is a health-based international crisis, the concept of mobility has been described as illegal for a long time around the world. The change in the policies adopted by the source and destination countries, caused by the forced inactivity, created permanent and temporary effects on the immigrants, who are the subject of migration, and interrupted the existing migration flow. The change in the movement ideas of immigrants, which determines the direction of this migration flow, which was interrupted after the pandemic, will be examined in the context of Covid-19.
Keywords: International economic relations; International relations; Kovid-19; Political science; Siyasal bilim; Uluslararası ekonomik ilişkiler; Uluslararası ilişkiler; Yer Değiştirme Tercihi Covid-19